Effects of Digitalization on Natural Resource Use in European Countries: Does Economic Complexity Matter? - Mai, Ngô Thanh; Ha, Le Thanh; Hoa, Trần Thi Mai; Huyen, Nguyen Thi Thanh (International Journal of Energy Economics and Policy, 2022)
This paper empirically analyses the influences of the digital transformation process in the business and public sector on natural resources rents. Our paper employs the digital businesses (e-Commerce, including the value of online selling, e-Commerce turnover, e-Commerce web sales, and e-Business, including customer relationship management (CRM) usage and cloud usage) and the digital public services (user-centricity, business mobility, and key enablers), while we deal with the total natural rents (coal rents, mineral rents, natural gas rents, and forest rents). The various econometric techniques are applied to a sample of 26 European Union countries during the 2011-2019 period. Our estimation results demonstrate that both digital businesses and digital public services lead to a rise in total natural rents. More specifically, the digital businesses appear to have increased influences on coal rents, and gas rents, while the digital public services drive mineral rents, gas rents, and forest rents up. Conversely, digital public services tend to reduce coal rents and digital businesses lead to a decrease in mineral rents and forest rents. Notably, the economic complexity or the quality and diversification of the production system is the key variable for the digital economy aiming at shirking natural rent-seeking. The findings are consistent when we consider the specific type of natural resource rent regardless of whether they are affected differently by digital transformation.